A descriptive case study on Filipino millennials' preferences on the interior design of studio Airbnb spaces - Tahil, Rachelle Mae A.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
The research was motivated by the growing popularity of Airbnb in the sharing economy, particularly among millennials seeking unique and affordable travel experiences. This study explored the preferences of Filipino millennials regarding the interior design of studio Airbnb spaces in Metro Manila. The study objectives were to describe the existing interior design elements present in the selected studio Airbnb spaces, identify the Filipino millennials' preferences on the interior design of studio Airbnb spaces in Metro Manila, and provide recommendations for improving the interior design of studio Airbnb spaces in Metro Manila. A convenient and purposive sampling approach was used to select six participants residing in Metro Manila, aged between 22 and 42 years, and with at least two Airbnb experiences in the last five years. Questionnaires and interviews were conducted to gather data based on criteria such as lighting, color scheme, space layout, furniture, amenities, and decorative accessories. The study revealed that Filipino millennials' preferences were influenced by their values, lifestyle choices, and comfort. Of the three, comfort was the most important factor in determining the interior design preferences of Filipino millennials. The findings may contribute to the understanding of interior design preferences of Filipino millennials and offer practical solutions for Airbnb hosts and designers in creating spaces that meet the comfort needs and preferences of Filipino millennials, ultimately enhancing guest satisfaction and overall experiences.
Thesis
Bibliography: pages 113-122.
Keywords: Consumers' preferences -- Philippines -- Metro Manila; Generation Y -- Philippines -- Metro Manila; Interior decoration -- Philippines -- Metro Manila